Gut microbiota dysbiosis: The potential mechanisms by which alcohol disrupts gut and brain functions - Chen, Ganggang; Shi, Fenglei; Yin, Wei; Guo, Yao; Liu, Anru; Shuai, Jiacheng; Sun, Jinhao (Frontiers in Microbiology, 2022)
Alcohol use disorder (AUD) is a high-risk psychiatric disorder and a key cause of death and disability in individuals. In the development of AUD, there is a connection known as the microbiota-gut-brain axis, where alcohol use disrupts the gut barrier, resulting in changes in intestinal permeability as well as the gut microbiota composition, which in turn impairs brain function and worsens the patient’s mental status and gut activity. Potential mechanisms are explored by which alcohol alters gut and brain function through the effects of the gut microbiota and their metabolites on immune and inflammatory pathways. Alcohol and microbiota dysregulation regulating neurotransmitter release, including DA, 5-HT, and GABA, are also discussed. Thus, based on the above discussion, it is possible to speculate on the gut microbiota as an underlying target for the treatment of diseases associated with alcohol addiction. This review will focus more on how alcohol and gut microbiota affect the structure and function of the gut and brain, specific changes in the composition of the gut microbiota, and some measures to mitigate the changes caused by alcohol exposure. This leads to a potential intervention for alcohol addiction through fecal microbiota transplantation, which could normalize the disruption of gut microbiota after AUD.